Analysis of the Effectiveness of the Integrated Public Service Information System at the Department of Population and Civil Registration (Dukcapil) - Leo Saputra Hulu; I Ketut Sudaryana (Jurnal Komputer, Informasi dan Teknologi, 2025)
The development of information technology has encouraged government agencies, including the Population and Civil Registration Service (Dukcapil), to adopt a digital-based public service information system. This study aims to analyze the effectiveness of the integrated public service information system at Dukcapil using the DeLone & McLean model which includes six dimensions: system quality, information quality, service quality, usage, user satisfaction, and net benefits. The research method used is descriptive qualitative through interviews and observations. The results of the study indicate that the information system has helped speed up the service process and increase transparency, but there are still obstacles such as an unfriendly system interface, data errors, low adoption of Digital Population Identity (IKD), and literacy gaps. digital access in the community. This study recommends improving system quality, training officers, expanding IKD socialization, and strengthening digital education for vulnerable groups to ensure equitable and optimal access to services.